2023
DOI: 10.3390/agronomy13030621
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Cytokinin and UV-C Light on Phenolic Pattern in Ceratonia siliqua Shoot Cultures

Abstract: Carob (Ceratonia siliqua L.) is an underutilized traditional crop in the Mediterranean regions that has gained much interest due to its high nutritional traits and resilience to drought and salinity. However, conventional methods of carob propagation are not enough to meet its increasing market demands. The present study analyzes to what extent benzyl adenine (BA) treatments (0.1, 0.5 and 1.0 mg L−1) alone or in combination with UV-C irradiation (3.34 and 10.01 kJ m−2) affect the antioxidant capacity and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Moreover, it is worth mentioning that, apart from metal chelating activity, TPC showed no correlation with the rest of the antioxidant assays analyzed. Studies on the relationship between TPC and antioxidant activities show contradictory results; whereas some authors have reported high correlation values [29,47,48], others found no correlation between these parameters [39,49]. These results suggest that phenolic compounds are not the only contributors to the antioxidant activities in some plant extracts, and other phytochemicals could also contribute to the total antioxidant activity of these extracts.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, it is worth mentioning that, apart from metal chelating activity, TPC showed no correlation with the rest of the antioxidant assays analyzed. Studies on the relationship between TPC and antioxidant activities show contradictory results; whereas some authors have reported high correlation values [29,47,48], others found no correlation between these parameters [39,49]. These results suggest that phenolic compounds are not the only contributors to the antioxidant activities in some plant extracts, and other phytochemicals could also contribute to the total antioxidant activity of these extracts.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of bioactive compounds in dates has attracted considerable attention from researchers, positioning this fruit as a promising natural source of antioxidants and functional food ingredients [ 76 ]. Additionally, studies have explored the effectiveness of UV-C irradiation in improving the quality and extending the shelf life of fruits and vegetables [ 2 , 77 , 78 , 79 ]. However, there is currently little information on the potential application of UV-C rays in the processing of second-grade dates.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that UV-C and gamma radiation have an impact on a variety of medicinal plants cultivated in vitro. The decrease in shoot formation at increased UV-C and gamma radiations may be due to oxidative stress induction and irrevocable toxic effects on cells that can promote the breakdown of cells in plant culture (Costa-Pérez et al, 2023). Moreover, prolonged exposure to intense light stress causes plants' photosynthetic mechanisms to become photo-inhibited (Pujari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%